Endovascular management of dural fistulas into the cavernous sinus - Luis Rafael Moscote-Salazar; Marco Zenteno; Jorge A. Santos-Franco; Nancy Carolina Duarte-Valdivieso; Hernando Raphael Alvis-Miranda; Angel Lee (Romanian Neurosurgery, 2014)
Background: Dural fistula to the cavernous sinus (DFCS) is an infrequent pathology that consists in the anomalous communication between the meningeal branches of the internal carotid artery (ICA) and/or the external carotid artery (ECA) and the cavernous sinus. Aim: To perform a systematic review to evaluate clinical and imaging findings in DFCS, and current indications for treatment. Methods: A literature search was performed in several medical databases using the keywords “intracranial dural fistula”, “carotid-cavernous fistula”, “endovascular treatment”, associated with “outcome”; resulting articles were assessed by considering factors such as: number of patients treated, type of material used, complications, and type of image technique used for diagnosis. Results: 33 articles were selected, yielding: clinical and imaging: The symptoms are basically related to the type of venous drainage of the fistula. The combination of ocular symptoms and tinnitus is highly suggestive of DFCS. Ocular symptoms are found in 80-97% of patients, while the tinnitus is present in up to 50% of cases. The imaging method for initial assessment of the DFCS is the magnetic resonance imaging. Digital subtraction angiography is the method of choice to determine adequately the precise angioarchitecture of the injury and its drainage. This data is of vital importance in future decision making. Treatment: Currently are considered as indications for the management of DFCS: 1) rapidly progressive deterioration of visual function, 2) angiographic evidence of abnormal cortical venous drainage, 3) the hypoxic consequences in retina and optic nerve, and 4) ischemic keratitis; the most suitable materials for embolization of the DFCS are CA and PAP. Conclusion: DFCS stills being an uncommon cerebrovascular condition, with good outcomes from endovascular treatment.